The existence of God - Swinburne, Richard (Clarendon Press ; Oxford University Press, 1991)
This book is based on the author's Wilde Lectures delivered in the University of Oxford in 1976-7. It forms part of a trilogy which began with The Coherence of Theism (Clarendon Press, 1977, reissued in paperback, 1986) and was completed by Faith and Reason (Clarendon Press, 1981, reissued in paperback, 1983), but it does not in any way presuppose knowledge of the earlier work. For the revised fifth impression of the paperback edition, Professor Swinburne has added a new preface, and two new appendices: one a reply to Mackie and one a discussion of the argument from 'fine tuning'.